2023
DOI: 10.1002/jev2.12358
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of human brain‐derived extracellular vesicles using multiple isolation methods: Implications for diagnostic and therapeutic applications

Abstract: Extracellular vesicles (EVs) have emerged as critical mediators of intercellular communication and promising biomarkers and therapeutics in the central nervous system (CNS). Human brain‐derived EVs (BDEVs) provide a comprehensive snapshot of physiological changes in the brain's environment, however, the isolation of BDEVs and the comparison of different methods for this purpose have not been fully investigated. In this study, we compared the yield, morphology, subtypes and protein cargo composition of EVs isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Additional results obtained by fluorescent confocal microscopy and FCA confirmed the sorting of L1CAM extraluminal epitopes to bona fide single NDEVs carrying the canonical EV markers Alix and tetraspanins CD9, CD63 and CD81 (Figure 1d–o ). Particularly, FCA results showed that a vast majority of L1CAM+ EVs from iNeurons co‐express the synaptic protein VAMP2 (Figure 1o ), previously reported to be enriched in EVs secreted by mice, rat and human neurons (Vilcaes et al., 2021 ; You et al., 2022 ), and differentiating them from glia‐derived EVs (You et al., 2022 ; Zhang et al., 2023 ). Our findings at the single EV level validate previous studies detecting L1CAM in EVs from neuronal culture media via immunoblotting, L1CAM Simoa ® of SEC EV fractions and mass spectrometry (Faure et al., 2006 ; Lachenal et al., 2011 ; Norman et al., 2021 ; Vilcaes et al., 2021 ).…”
Section: Discussionmentioning
confidence: 72%
“…Additional results obtained by fluorescent confocal microscopy and FCA confirmed the sorting of L1CAM extraluminal epitopes to bona fide single NDEVs carrying the canonical EV markers Alix and tetraspanins CD9, CD63 and CD81 (Figure 1d–o ). Particularly, FCA results showed that a vast majority of L1CAM+ EVs from iNeurons co‐express the synaptic protein VAMP2 (Figure 1o ), previously reported to be enriched in EVs secreted by mice, rat and human neurons (Vilcaes et al., 2021 ; You et al., 2022 ), and differentiating them from glia‐derived EVs (You et al., 2022 ; Zhang et al., 2023 ). Our findings at the single EV level validate previous studies detecting L1CAM in EVs from neuronal culture media via immunoblotting, L1CAM Simoa ® of SEC EV fractions and mass spectrometry (Faure et al., 2006 ; Lachenal et al., 2011 ; Norman et al., 2021 ; Vilcaes et al., 2021 ).…”
Section: Discussionmentioning
confidence: 72%
“…We found a strong enrichment of known EV markers and a reduction of plasma, nuclear, cytosolic, and most mitochondrial proteins. A recent study comparing three CNS tissue EV separation protocols—SEC, sucrose gradient ultracentrifugation, and phosphatidylserine affinity capture—highlighted the speed and robustness of SEC, but also reported contamination with soluble proteins using this method [ 42 ]. However, our protocol differs from this publication in several steps: we carried out filtration with a smaller cut-off (0.22 µM vs 0.45 µM) and used higher centrifugation speeds to eliminate larger EVs—which reduces contamination and refines the studied EV subset.…”
Section: Discussionmentioning
confidence: 99%
“…This variance in miRNA uctuations might root from the diversity in exosomes origins. Considering exosomes can emerge from a variety of organs, with those stemming from neurons forming just a minute segment, this distinction is not entirely surprising [15]. Compounding the complexity, prior research often hinges on smaller participant groups and tends to focus on a con ned set of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…While prior studies con rm altered miRNAs in blood exosomes of patients with mental disorders [12][13][14], it's important to note that the origin of these exosomes in peripheral blood is multifaceted. Only a minimal fraction is sourced directly from brain tissue [15]. However, a breakthrough is the capability to concentrate neuron-derived exosomes from blood samples.…”
Section: Introductionmentioning
confidence: 99%